2014
DOI: 10.4236/ajps.2014.515246
|View full text |Cite
|
Sign up to set email alerts
|

Response of Fodder Maize to Various Levels of Nitrogen and Phosphorus

Abstract: A. Khan et al. 2324 fertilizers have a positive effect on the fodder yield of maize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 6 publications
(5 reference statements)
7
21
0
Order By: Relevance
“…Similar results were observed regarding chlorophyll content (Table 1), LAI and relative photosynthetic potential for grain yield/plant (Table 3), Plant height and ear leaf area (Table 2), ear length and stem diameter (Table 4), row number/ear and grain number/row as well as hundred grain weight (Table 5) and grain yield/ plant and biological yield/ plant. These results are in agreement with those reported by Khan et al (2005), Ahmad et al (2007), Hussein (2009) and Khan et al (2014) as they reported significant increase in grain and biological yields/ fad., due to addition of P up to level of (60, 90 , 120 kg P 2 O 5 ha -1 ), respectively.…”
Section: Phosphors Level Effectsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results were observed regarding chlorophyll content (Table 1), LAI and relative photosynthetic potential for grain yield/plant (Table 3), Plant height and ear leaf area (Table 2), ear length and stem diameter (Table 4), row number/ear and grain number/row as well as hundred grain weight (Table 5) and grain yield/ plant and biological yield/ plant. These results are in agreement with those reported by Khan et al (2005), Ahmad et al (2007), Hussein (2009) and Khan et al (2014) as they reported significant increase in grain and biological yields/ fad., due to addition of P up to level of (60, 90 , 120 kg P 2 O 5 ha -1 ), respectively.…”
Section: Phosphors Level Effectsupporting
confidence: 93%
“…Based on the combined data, adding 15.5 and 31 kg P 2 O 5 / fed., increased ear leaf area by 11.08 and 17.89%, receptively. These results are similar to those proved by Mukhtar et al (2011), Khan et al (2014) and Olusegun (2015).…”
Section: Phosphors Level Effectsupporting
confidence: 93%
See 1 more Smart Citation
“…It is a heavily applied nutrient in agricultural crops and farmers mostly rely on N (Khan et al 2014;Amanullah et al 2016;Hafiz et al 2016;Yousaf et al 2016a, b;Wajid et al 2015). N is needed to establish leaf canopy growth for light interception and utilization and photosynthesis .…”
Section: Nitrogen Fertilizationmentioning
confidence: 99%
“…Numerous experiments have been conducted to identify nutrient use efficiency as N-efficient use cultivars will be cost-effective and environment friendly for growers by reducing the excessive input cost (Afridi et al 2014;Canfield et al 2010). N fertilizer management takes into account all natural methods accountable for N loss.…”
Section: Management Decisionsmentioning
confidence: 99%